2021
DOI: 10.1061/(asce)st.1943-541x.0003089
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Steel Moment Frames Using Top-and-Seat Angle Connections under Various Column-Removal Scenarios

Abstract: Behavior of Steel Moment Frames using Top-and-Seat Angle Connections under Various Column Removal Scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It is simply assumed that each story has identical geometric and material properties and thus, assuming each story performed identically. However, as pointed out by Qian et al (2020), Qian et al (2021b), andWeng et al (2020), the load resistance of the beams in the first story is quite different to the second and upper stories. It could be explained that the interaction among different stories, which leads to different mobilization of load resisting mechanisms (flexural and catenary action).…”
Section: Introductionmentioning
confidence: 92%
“…It is simply assumed that each story has identical geometric and material properties and thus, assuming each story performed identically. However, as pointed out by Qian et al (2020), Qian et al (2021b), andWeng et al (2020), the load resistance of the beams in the first story is quite different to the second and upper stories. It could be explained that the interaction among different stories, which leads to different mobilization of load resisting mechanisms (flexural and catenary action).…”
Section: Introductionmentioning
confidence: 92%
“…Comparison of the collapse resistance between single-story frames and multi-story frames revealed that the collapse resistance between two different structural scale models is not based on the number of stories because of the existence of Vierendeel action (VA) [16][17][18]. Qian et al [19][20], Tsito et al [21] and Zhong et al [22] have conducted quasi-static collapse tests, and subsequently, compared and analyzed in detail the influence of connection type, failure column position, and other parameters on the structural performance. Their results show that the connection types and failure column position exhibit a considerable influence on the exertion of catenary action.…”
Section: Introductionmentioning
confidence: 99%
“…The research on the progressive collapse resistance of structures has been a hot topic worldwide for many years due to the partial or total collapse of iconic and public buildings [1][2][3][4][5][6][7][8]. There are numerous studies about the progressive collapse behavior of reinforced concrete [9][10][11][12][13] and steel frame structures [14][15][16][17]. The collapses of long-span spatial structures, especially for the spatial truss structures caused by member failure, may lead to more losses.…”
Section: Introductionmentioning
confidence: 99%